The Analysis of Organizational Changes using Structural Equation Modelling with Mediating Readiness to Change in Higher Education - Rindang Ayu; Nurul-Azza Abdullah; Wan Shahrazad Wan Sulaiman; Mohd Nasir Bin Selamat (JOIV : International Journal on Informatics Visualization, 2023)
This research study demonstrates that the readiness to change moderates the association between supervisor support and commitment to organizational change. The variable "readiness to change" fulfills this moderating function. The State University in West Sumatra, a prestigious institution of higher education in Indonesia, boasts a faculty comprising 260 committed teaching personnel. The formulation of the questionnaire was grounded upon a predetermined set of criteria. The data analysis process involved utilizing Structural Equation Modelling (SEM) and SmartPLS 3.0 software. The results obtained from using structural equation modeling (SEM) were consistent with recognized metrics such as Cronbach alpha, composite reliability, mean-variance extracted, and evaluation criteria for both measurement and structural models. Furthermore, it also showcased the soundness and reliability of the measurement instruments. The study suggests that the mediating factor of preparation for change plays a role in the association between the provision of high-quality support and the level of commitment towards organizational change. This study contributes to the field of management and organizational leadership by providing insights on how to develop robust change strategies through enhancing employees' readiness for transition. This study makes a valuable contribution to the field of change management by emphasizing the role of readiness to change as a mediating factor in the relationship between supervisor support and organizational change commitment. This research additionally aids organizations in developing grooming and training programs aimed at equipping employees with the necessary skills and knowledge to adapt to change.